Crystallization of tricalcium silicate blended with different silica powder dosages at high temperature. (17th January 2022) - Wei, Tingcong; Cheng, Xiaowei; Liu, Huiting; Zhang, Hua; Zhang, Liwei; Mei, Kaiyuan; Zhang, Chunmei; Liu, Kaiqiang; Zhuang, Jia
Highlights: With increasing silica powder dosage, high calcium-silicon ratio phases decreased. Dense structure composed of xonotlite was beneficial to mechanical properties. Hillebrandite, jaffeite, reinhardbraunsite and xonotlite were all single crystals. Xonotlite was formed by decalcification reaction and Si-OH polymerization. Abstract: The effect of silica powder dosage on the mechanical properties and microstructure of C3 S, especially on the crystallization transformation of hydration products, was studied by VHT, XRD, TGA, SEM-EDS and TEM. The results showed that at 230 °C, the optimal amount of silica powder added was 40%, and the Vickers hardness increased by 39.21%. With increasing silica powder dosage, the contents of hillebrandite, jaffeite, and reinhardbraunsite continued to decrease, and the content of xonotlite continued to increase. Coarseness of the microstructure at high temperature was the main reason for the deterioration of mechanical properties, and the dense structure composed of xonotlite was beneficial to improve the mechanical properties. The microscopic morphology and crystal structure of hillebrandite, jaffeite, reinhardbraunsite and xonotlite were confirmed. These hydration products were all single crystals. C-S-H in the C3 S-silica powder system decalcified and produced large amounts of Si–OH, and silica powder obtained calcium from C-S-H. Si–OH on the surface of silica powder polymerized with Si–OH in decalcified C-S-H or interacted with silicate ions in the hydration system, which formed xonotlite.